Interactive Digital Advertising as a Strategy to Increase Brand Awareness, Engagement, and Purchase Intention in Local Startups: A Conceptual Study - Arlindo do Ceu Fatima; Casimirio Soares; Gupron, Gupron; M. Ridho Mahaputra; Andri Yandi (Siber International Journal of Digital Business (SIJDB), 2025)
The development of digital technology has encouraged local startups to adopt more effective and efficient marketing strategies. One increasingly used approach is interactive digital advertising, which enables two-way communication between brands and consumers. This conceptual article aims to examine the role of interactive digital advertising in increasing brand awareness, consumer engagement, and purchase intention. By integrating various previous research findings, this article develops a conceptual framework that demonstrates the relationship between interactive digital advertising and brand awareness, consumer engagement, and purchase intention. This study is expected to provide theoretical contributions to the development of sustainable marketing literature and serve as an initial reference for researchers in conducting future empirical research.